2017
DOI: 10.1186/s12888-016-1169-y
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reduce the stigma toward people with mental disorders in Iran: stakeholders’ perspectives

Abstract: BackgroundStigma affects all aspects of mental disorders, and is the most important risk factor for promoting mental health. The aim of this study was to explore strategies effective in reducing the stigma toward people with mental disorders in Iran.MethodsThis qualitative study was conducted from 2013 to 2016. All participants were recruited by purposive sampling method. The majority of them were stakeholders of mental health in Iran. Data were collected through eight individual interviews, two focus groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 41 publications
0
60
0
1
Order By: Relevance
“…While we were able to link pollution exposures to the primary care record to obtain diagnoses of dementia, there are concerns around the variability of dementia diagnoses in UK primary care, 24 and a recent review has concluded that dementia diagnoses on primary care databases may not be an accurate reflection of the true prevalence. 25 Under-recording is thought to be a common issue, as the diagnosis is associated with a stigma for many, and GPs may be reluctant to diagnose dementia unless highly certain. 26 A recent study across 23 London practices increased the prevalence on their QOF dementia registers by 9% by a simple coding review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we were able to link pollution exposures to the primary care record to obtain diagnoses of dementia, there are concerns around the variability of dementia diagnoses in UK primary care, 24 and a recent review has concluded that dementia diagnoses on primary care databases may not be an accurate reflection of the true prevalence. 25 Under-recording is thought to be a common issue, as the diagnosis is associated with a stigma for many, and GPs may be reluctant to diagnose dementia unless highly certain. 26 A recent study across 23 London practices increased the prevalence on their QOF dementia registers by 9% by a simple coding review.…”
Section: Discussionmentioning
confidence: 99%
“…Future large-scale studies will need to rely on improved recording and linkage of dementia diagnoses across electronic systems, particularly Alzheimer’s disease, where multiple sources can improve diagnostic accuracy. 25 Since exposure is lifelong, and most cases are diagnosed in later life, historical data are also ideally required to better estimate cumulative exposure over preceding decades. In conclusion, our findings add to a growing evidence base linking air pollution and neurodegeneration and should encourage further research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of various research projects on stigma reduction programs, few studies have examined how to overcome stigma toward family caregivers of mental illness patients [ 14 , 15 ]. It seems that the stigma reduction strategies vary according to the contextual factors including politics, socioeconomic status, culture, religion and media.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the stigma reduction strategies vary according to the contextual factors including politics, socioeconomic status, culture, religion and media. Iran is a Middle-East Islamic country with an approximately 79-million population [ 15 ] in which religious culture is dominant. In Iran, families play the key role in taking care of the mental illness patients, and social variables as well as the misbeliefs of people pose them some problems such as stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Nongovernmental organizations (NGO) focusing on mental health are few. For example, Taghva et al,. (2017) found that there are very few NGOs in Iran and they do not play an active role in stigma reduction.…”
mentioning
confidence: 99%